Makna Qanaah dalam Menjalani Peran Sebagai Orang Tua Anak dengan Autism Spectrum Disorder (ASD) - Anis Anjar Subekti; Triyono (Psychopolytan : Jurnal Psikologi, 2026)
Parents of children with Autism Spectrum Disorder (ASD) face emotional, social, and spiritual pressures in the caregiving process, which require inner resilience to accept their child’s condition. One spiritual value that supports this process is qanaah, defined as conscious acceptance of Allah’s decree accompanied by continuous effort. This study aims to explore the meaning of qanaah based on the lived experiences of parents of children with ASD at UPTD PLDPI, Surakarta City. This study employed a qualitative phenomenological approach. Participants were purposively selected and consisted of four parents as primary informants and three therapists as supporting informants. Data were collected through semi-structured interviews, non-participant observation, and documentation, and were analyzed using Interpretative Phenomenological Analysis (IPA). The results show that qanaah is understood as an active acceptance that helps parents carry out caregiving in a calmer and more meaningful way. Qanaah is formed through acceptance of Allah’s decree, patience and sincerity, a balance between effort and reliance on God (tawakal), as well as inner peace strengthened by social support and religious practices. These findings emphasize the importance of spiritually strengthened family support programs in enhancing the psychological resilience of parents of children with special needs.